Role of Synthesis Route on The Structural and Photocatalytic Activity of Magnetic TUD-1 Coated NiFe2O4 - Suresh Sagadevan; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali; Won-Chun Oh; Ruey-an Doong; Is Fatimah; Hiroko Kawaii Wijayanti (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
In this research, TUD-1 coated NiFe2O4 was synthesized by comparing in-situ and post- synthesis methods, for application as photocatalyst material in dye degradation. One pot synthesis of material was conducted by mixing all chemical precursors in a homogeneous system under hydrothermal condition, followed by calcination at 500oC for 2h. For comparison purpose, two-steps synthesis procedure conducted by firstly synthesis of TUD-1 followed by its use for NiFe2O4 impregnation. Tetraethyl orthosilicate (TEOS) was employed as precursor for TUD-1 and NiCl2.6H2O and FeCl3.6H2O were utilized as precursors for synthesis of NiFe2O4 by co-precipitation method. The physicochemical properties of materials were characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Gas Sorption Analyzer (GSA), zeta potential, Vibrating-Sample Magnetometry (VSM) and Ultraviolet-Diffuse Reflectance (UV-DRS). The photocatalytic activity examination of materials was conducted for methylene blue (MB) and rhodamine B (RhB) photocatalytic oxidation. The results indicated that in-situ prepared material (NFT-1) produced a higher specific surface area of 228.75 m2/g compared to post-synthesis material (NFT-2) with the value of 218.07 m2/g. The NFT-1 material exhibited band gap energy of 2.73 eV which support adsorption capacity and photocatalytic activity. An excellent degradation of MB of 95.67% removal and RhB of 95.08% removal during 60 min were demonstrated by NFT-1. The materials showed magnetism to support easy in separation and reusability. Based on the reusability results, the synthesized material has maintained stability until 5th cycles. Evaluation on the effect of scavengers on the kinetics of photocatalytic degradation has been performed and the hydroxyl radicals (●OH) was proven to be the most important species for the oxidation mechanism. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).